Research on the impact mechanism of comprehensive land consolidation on rural human settlement environment based on the production-living-ecological space theory: a case study of Zhejiang Province, China - Meng, Lin; Yan, Fengjuan (Frontiers in Public Health, 2025)
Exploring the influence mechanism of Comprehensive Land Consolidation (CLC) on the quality of Rural Human Settlement Environments (RHSE) is essential for advancing theoretical and methodological advancements in RHSE improvement. Additionally, this study provides a reference for implementing China’s rural revitalization strategy and advancing CLC pilot programs. In this article, Zhejiang Province was selected as the research area, where entropy methods, geographic detectors, and other analytical tools were employed to examine the impact mechanisms of CLC on RHSE. Policy recommendations were proposed based on the findings. The results showed that: (1) At both the provincial and municipal levels, both RHSE and CLC exhibited significant improvements in Zhejiang from 2000 to 2020, confirming the pivotal role of CLC in enhancing RHSE quality. (2) The single factor detection results of the geographic detector indicated that CLC has high explanatory power for improving RHSE quality by promoting an increases in average grain yield per mu, public land area, land use elasticity, effective irrigation rate, concentrated and contiguous farmland, land reclamation rate, and other factors. The results revealed the important role of CLC in improving the average grain yield per mu, effective irrigation rate, concentrated contiguous farmland, and land reclamation rate in driving RHSE development. (3) Based on the research results, various CLC policies can be implemented to improve the RHSE. The government can integrate high-standard farmland construction to enhance the potential for agricultural development. Meanwhile, policies can be formulated to promote industrial chain extension and advance infrastructure construction. Additionally, policies can be proposed to raise awareness of vegetation protection and improve ecological restoration work